Research of the Geomorphology Sector of the Institute of Geography of NAS of Ukraine in the First Quarter of the 21st Century - Spytsia, R. O.; Bahmet, O. B. (Ukrainian Geographical Journal, 2024)
The creation of the Ukrainian Academy of Sciences in 1918 marked the beginning of a more than a century-long period of systematic geomorphological research on the territory of Ukraine. In 1961, at the Institute of Geological Sciences of the Academy of Sciences of the Ukrainian SSR, the department of the latest movements of the earth’s crust began work, which was transformed over time into the department (since 2016 - the sector) of geomorphology of the Institute of Geography of the National Academy of Sciences of Ukraine. During the second half of the 20th century, the main areas of fundamental, regional and applied geomorphological and neotectonic research were formed in the Department of Geomorphology. At the end of the 20th century the introduction of geoinformation analysis and modeling methods into scientific research, which became an impetus for the modernization of existing and the creation of new effective methods for researching the relief, relief-forming deposits, the latest and modern dynamics of the near-surface part of the lithosphere. Among the main directions of research of the department of geomorphology in the first quarter of the 21st century should be mentioned the study of spatio-temporal regularities and factors of modern (including anthropogenic) geomorphogenesis, the study of the latest and modern dynamics of the near-surface part of the lithosphere, the development of methods for the detection, ranking and assessment of the neogeodynamic rating of linear morphostructures, applied engineering-geomorphological, ecological-geomorphological and prospecting-geomorphological studies, large-scale geomorphological and neotectonic mapping and geoinformation modeling. Armed Russian aggression, as a result of which large-scale transformations of the relief took place, made corrections in the directions of geomorphological studies of the sector. In the near future, applied geomorphological studies with the aim of post-war restoration of geomorphological systems will be relevant.
Keywords: geomorphology; neotectonics; relief; fundamental, regional, and applied research; geoinformation geomorphological mapping